2004
DOI: 10.1097/01.tp.0000114291.01231.dd
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and chronic rejection: A study in kidney transplant long-term survivors

Abstract: We observed that a match for class I and class II HLA antigens apparently does not favor the long-term survival of transplanted kidneys. In fact, matched grafts are lost before 10 years in the same proportion as the mismatched grafts. We also demonstrated (1) that patients who are homozygous for GG at the SNP -1082IL10 (high IL-10 producers) and HLA class I mismatched (but matched for class II) are protected from chronic rejection, and (2) that patients who are homozygous for CC at the SNP -33IL4 (low IL-4 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…These results are consistent with the conception that the Th1 response is generally associated with rejection, whereas the Th2 response may lead to tolerance of transplant [11,12]. Our results are also consistent with other reports showing a significant association of IL4 gene polymorphisms with ACR following kidney or heart transplantation [1,7,10,16,18].…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…These results are consistent with the conception that the Th1 response is generally associated with rejection, whereas the Th2 response may lead to tolerance of transplant [11,12]. Our results are also consistent with other reports showing a significant association of IL4 gene polymorphisms with ACR following kidney or heart transplantation [1,7,10,16,18].…”
Section: Discussionsupporting
confidence: 96%
“…Cytokine genotypes have been previously studied in patients who have undergone solid organ transplantation, and certain polymorphisms have been found to affect the development in graft rejection [1][2][3][4][5][6][7][8][9][10]. In the field of organ transplantation, pro-inflammatory Th1 cytokines are believed to be involved in acute transplant rejection, by directly contributing to graft damage.…”
Section: Introductionmentioning
confidence: 98%
“…42 In clinical situations they are involved in chronic inflammation and fibrosis. 15,16 On the other hand, studies have demonstrated a protective effect of Th2 cytokines on the allograft. Th2 cytokines, especially IL-4, are necessary for induction of the allograft tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…14,15 Chronic rejection in renal transplantation was associated with high levels of IL-4. 16 Chemokines and their interaction with specific cell receptors are essential components of any immune responses through the recruitment of specific leukocyte sub-populations. Understanding the immunologic processes that are involved in the development of BOS is an essential pre-requisite for ultimate improvement of longterm survival after lung transplantation.…”
mentioning
confidence: 99%
“…Citation No association TNF -308G>A rs1800629 Sankaran et al, 1999;Pelletier et al, 2000;Poli et al, 2000;Hahn et al, 2001;Reviron et al, 2001;Wramner et al, 2004;Alakulppi et al, 2004;Grinyo et al, 2008;Pawlik et al, 2005;Tinckam et al, 2005;Lacha et al, 2005;Canossi et al, 2007;Coppo et al, 2007;Mendoza-Carrera et al, 2008;Nikolova et al, 2008;Pawlik et al, 2008;Grenda et al, 2009;La Manna et al, 2010;donor: Nikolova et al, 2008Hutchings et al, 2002Marshall et al, 2000;Cartwright et al, 2001;George et al, 2001;MullerSteinhardt et al, 2002;Weimer et al, 2003;McDaniel et al, 2003;Uboldi de Capei et al, 2004;Ligeiro et al, 2004;Dmitrienko et al, 2005;Gendzekhadze et al, 2006;Azarpira et al, 2006;Brabcova et al, 2007;Breulmann et al, 2007;Satoh et al, 2007;Rodrigo et al, 2007;Alakulppi et al, 2008;Azarpira et al, 2009;Kao et al, 2010;Jacobson et al, 2010;…”
Section: Gene Polymorphism Dbsnp Rs Number Citation Associationunclassified